EVALUASI PENGEMBANGAN TERMINAL PENUMPANG BANDAR UDARA HUSEIN SASTRANEGARA - Graha, Raden Griska Savitri; Santosa, Wimpy (Jurnal Transportasi, 2015)
AbstractÂ Husein Sastranegara Airport is located in Bandung. This airport has experienced growth in numbers of passengers and the number of passengers has exceeded the capacity of passenger terminal, so that the development of a passenger terminal is needed. The aim of this study is to evaluate the compliance of Husein Sastranegara Airportâs passenger terminal development to the criteria of the Indonesia National Standard (SNI) 03-7046-2004, about Passenger Terminal at Airports. The design of passenger terminal development is compared with the criteria stated in the SNI 03-7046-2004. The results show that the design of passenger terminal development does not fulfill the passenger terminal area needed for the design life of 20 years because there is a lack of area and facilities.Â Keywords: airport, passenger terminal, terminal capacity, terminal facilitiesÂ Â AbstrakÂ Bandar Udara Husein Sastranegara terletak di Kota Bandung. Bandar udara ini mengalami peningkatan jumlah penumpang setiap tahunnya dan peningkatan jumlah penumpang tersebut sudah melebihi kapasitas terminal penumpang yang ada, sehingga diperlukan pengembangan terminal penumpang. Tujuan penelitian ini adalah untuk mengevaluasi kesesuaian pengembangan terminal penumpang Bandar Udara Husein Sastranegara terhadap Standar Nasional Indonesia (SNI) 03-7046-2004, tentang Terminal Penumpang Bandar Udara. Desain pengembangan terminal penumpang Bandar Udara Husein Sastranegara dibandingkan dengan kriteria yang terdapat pada SNI 03-7046-2004. Dari hasil penelitian ini diperoleh bahwa desain pengembangan terminal penumpang tidak dapat memenuhi kebutuhan ruang terminal penumpang untuk umur perencanaan 20 tahun karena terdapat kekurangan ruang dan fasilitas.Â Kata-kata kunci: bandar udara, terminal penumpang, kapasitas terminal, fasilitas terminal